EFFECT OF PROTEIN TYPE AND SUGAR TYPE ON CHOCHOLATE PROPERTIES - Rifqi, Muhammad (EDUFORTECH)
This research aimed to investigate the effect of protein types (soy milk powder and skim milk powder) and sugar types (stevia and sucrose) on sensory properties of chocolate candy. The appropriate level of protein and sugar were also expected. The research performed using factorial randomized block design (RBD) with three replications. Factors namely ratio of protein type (soy milk powder, skim milk powder) and the ratio of sugar type (sucrose, stevia) were applied. Organoleptic response variables included taste, flavor, texture, and aftertaste were conducted using a hedonic test on 30 panelists. The results indicated that chocolate candy made from the ratio of soy milk with skim milk 0:1 and the ratio of sucrose and stevia of 1:1 gave the highest value of the organoleptic test. Proximate analysis showed the chocolate candy 11.05% fat, 13.44% protein, 25.28% carbohydrate, and water content of 1.17% and has a toughness test value of 1.23 mm/sec/100gram. This study revealed that alternative sugar (stevia) can be used in chocolate candy making and is expected to reduce calories contained on chocolate candy.